THE EGG PRODUCTION OF LAYING QUAIL WHICH WAS GIVEN MORINGA LEAF SOLUTION (Moringa oleifera L) INTO DRINKING WATER - Juarsa, Akhmad; Sudrajat, Deden; Anggraeni, Anggraeni (Jurnal Peternakan Nusantara, 2019)
This research was aimed to determine the effect of Moringa leaf solution on the production performance of laying quail (Coturnix-coturnix japonica). The livestock used in this research are 100 quails with the age of 35 day and average body weight 125,93 ± 3,056 g. The rations used were commercial period rations layer and drinking water mixed with Moringa leaf solution. The research design used was the Completely Randomized Designed with 4 treatments and 5 replications. The treatments given in this research are R0: drinking water without Moringa leaf solution, R1: drinking water + 5% of Moringa leaf solution, R2: drinking water + 10% Moringa leaf solution, R3: drinking water + 15% of Moringa leaf solution. The data obtained were analyzed using Analysis of Variance (ANOVA). The variables observed in this study were ration consumption, egg production, egg weight, egg mass production, ration conversion and mortality. Giving of Moringa leaf solution in quail did not significantly affect the ration and egg production, but it gave the effect on ration consumption, egg weight and egg mass production. Giving 5% of Moringa leaf solution can increase ration consumption, egg production, and improve the ration conversion and 0% mortality. Giving 15% Moringa leaf solution can increase the weight of the egg. Keywords: production performance, quail, Moringa leaf solution